NLRP3 regulates epithelial barrier integrity and protects from airway hyperresponsiveness in experimental allergic asthma - DeStefano, Stephanie; Grychtol, Ruth; Funken, Dominik; Habener, Anika; Tamm, Stephanie; Stanke, Frauke; Greiner, Wolfgang; Beyer, Kirsten; Hamelmann, Eckard; Kabesch, Michael; von Mutius, Erika; Schaub, Bianca; et al. (Frontiers in Immunology, 2025)
BackgroundThe inflammasome NLRP3 (NOD-like receptor family pyrin domain containing 3) is critical for epithelial barrier integrity. Allergic asthma is characterized by airway inflammation, airway hyperresponsiveness (AHR), and mucus hypersecretion. To date, the key players and underlying mechanisms in the interaction between NLRP3 and epithelial barrier integrity in type 2-mediated allergic asthma are poorly understood.ObjectiveOur study aims to evaluate the protective mechanisms of NLRP3 on airway epithelium and its structural and functional components during type 2-mediated allergic asthma inflammation.MethodsUsing an experimental model of allergic airway disease, NLRP3-deficient (NLRP3-/-) and wild-type (WT) mice were analyzed for AHR, mucus hyperplasia, airway inflammation and the alterations in the airway epithelium transcriptome.ResultsIn comparison to WT mice, NLRP3-/- mice exhibited significantly enhanced AHR and mucus production, while eosinophilic airway inflammation was comparable. Analysis of epithelial cell markers revealed decreased gene expression of the tight junction proteins Cld-18 and Tjp-1, and decreased expression of the epithelial transmembrane protein E-cadherin in the lungs of naïve NLRP3-/- mice compared to WT mice. Moreover, intranasal treatment with FITC-labelled OVA resulted in significantly higher allergen uptake by lung conventional dendritic cells (cDCs) in NLRP3-/- compared to WT mice indicating increased epithelial leakiness. In vitro, inhibition of NLRP3 in the human bronchial epithelial cell line 16HBE14o- with MCC950 resulted in the downregulation of Tjp-1 and CDH1 (E-cadherin).ConclusionNLRP3 is essential for epithelial barrier integrity in the lung and protects from the development of allergic asthma in a murine model.